FORMAÇÃO E AUTONOMIA DOCENTE: desafios à inclusão na educação infantil - Rodrigues, Gilvana Nascimento (2013)
The inclusion of children with disabilities in early childhood education has emerged as a challenge to teachers, who often consider themselves unprepared for this moment. The solitary work on the teacher produces a sense of helplessness preventing him from taking pedagogical decisions right ones. In comes the importance of teacher training, while articulating between inclusion in early childhood education and the construction of teaching autonomy towards a higher quality education. Thus , the present study aimed to analyze the contributions of continuing education to include children 4 and 5 years with disabilities in public schools of the city of São Luís / MA and specific objectives, knowing which thought the teachers about childhood in early childhood education and how this vision teacher can reflect on the inclusion process, identify the design of inclusive education built by teachers and their relation to a proposed school emancipatory and verify that the continuing education held in the school influences the pedagogical work of teachers. The research was based theoretically on the following authors: Imbernon (2009 and 2010) and Ramalho et.al (2003) and Adorno (1995) that authors were indispensable to reflect on the training of teachers; Januzzi (2006), Mendes (2006) and Costa (2011), among others, were supporters of the discussions about the inclusion of people with disabilities. With regard to early childhood education, Kuhlmann (2011), Oliveira (2008) and Kramer (2011) allowed us a better dialogue on the subject. As procedure for data collection, we used semi-structured interviews made twenty-one teachers of children aged 4 and 5 years belonging to the municipal public São Luís / MA, the qualitative approach. In this investigation it was established up by the results, continued education contributes to the process of inclusion of students with disabilities, as it enables a rethinking on the subject, which demystifies biased conceptions rooted in teachers as absolute truths, and proposes a teacher education for autonomy, in which clarification and experience are essential to the emancipation of the subject.